Serial MR diffusion to predict treatment response in high-grade pediatric brain tumors: a comparison of regional and voxel-based diffusion change metrics - Rodriguez Gutierrez, D.; Manita, M.; Jaspan, T.; Dineen, Robert A.; Grundy, Richard G.; Auer, Dorothee P. (Oxford University Press, 2013)
Background